2011
DOI: 10.1063/1.3661174
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant enhanced solid phase epitaxy of Ge/CaF2/Si(111): Synchrotron x-ray characterization of structure and morphology

Abstract: The structure and morphology of CaF2/Si(111) and Ge/CaF2/Si(111) layered structures with film thicknesses in the range of very few nanometers has been studied with synchrotron-based radiation. While the CaF2 film is grown via molecular beam epitaxy, the Ge film is fabricated by surfactant enhanced solid phase epitaxy with Sb as surfactant. The CaF2 film forms two laterally separated phases of relaxed CaF2 and pseudomorphic CaF2, respectively, although the film thickness is very homogeneous. The Ge film is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Therefore, relative changes in friction between samples can be determined quite accurately by using the same cantilever and tip during all measurements, as demonstrated by several authors. 4,15 In this work the V ph data extracted for each sample were the average values of six separate FFM measurements obtained from different surface regions. These measurements were typically performed in 1 × 1 μm 2 scan areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, relative changes in friction between samples can be determined quite accurately by using the same cantilever and tip during all measurements, as demonstrated by several authors. 4,15 In this work the V ph data extracted for each sample were the average values of six separate FFM measurements obtained from different surface regions. These measurements were typically performed in 1 × 1 μm 2 scan areas.…”
Section: Methodsmentioning
confidence: 99%
“…Semiconductor epitaxy using surface active species (surfactants), such as H, As, Sb, Te, or Sn, has attracted much interest during the last decades, mainly due to the possibility to suppress three-dimensional (3D) island growth for device applications. [1][2][3][4] In the particular case of III-V semiconductor molecular beam epitaxy (MBE) on (110)-oriented GaAs substrates, which finds application in the field of nonmagnetic spintronics, 5 it has been reported that the use of atomic hydrogen as a surfactant alters the kinetics of adatom incorporation to step edges, leading to two-dimensional (2D) layerby-layer growth of GaAs and 3D growth of InGaAs/GaAs quantum dots at low temperatures. [6][7][8] But the effect of this surfactant on the epilayer surface energy was not addressed in these studies.…”
Section: Introductionmentioning
confidence: 99%